A linguística no tempo: pontos de vista sobre a linguagem - Fuzer, Cristiane (Linguagens & Cidadania, 2017)
Different views on language from previously held conceptions have provided new relationships between this object of study and the subjects. Presenting some of these points of view in order to trace the historical course of linguistic studies is the purpose of this paper. The criterion used to select theories takes into account factors that seem to express nuances among them, aiming to point out some aspects of the development of linguistics before and after its acknowledgement as a science. The knowledge of these conceptions leads us to conclude that it is impossible to undertake any kind of linguistic study denying the relevance of previous studies. Thus, the role of contemporary linguists is as complex as the role of Greek and Roman philosophers, medieval grammarians and neogrammarians.